Implementasi Metode Network Development Life Cycle Pada Rancang Bangun Jaringan Wireless Berbasis Mikrotik - Putri Nirmalsari; Hairul Fahmi; Sofiansyah Fadli (Pusat Riset dan Inovasi Nasional, 2023)
As a non-departmental government agency (LPND) the Zainuddin Abdul Madjid Meteorological Station located at Lombok International Airport Zainuddin Abdul Madjid is one of the government agencies that is engaged in meteorology, namely conducting research related to climate change, early warning especially for the West Nusa Tenggara region. West Nusa Tenggara). In this study using data collection methods namely methods of observation, interviews, literature study and using the Network Development Life Cycle (NDLC) as a method of network design/development. There are several problems encountered within the internal scope, namely in increasing the comfort of staff using the internet network which has an unstable signal for the process of exchanging data resulting in one path of using the internet network there is one username and password that is used simultaneously by all staff and guests so that it makes the internet connection less stable. So this study aims to improve the system by resetting the existing proxy at the Zainuddin Abdul Madjid Meteorological Station office and creating usernames and passwords for staff and guests who have their own bandwidth.